Mediación pedagógica para la integración de tecnologías geoespaciales en la Cátedra de Sistemas de Información Geográfica (Repertorio Científico, 2024)
This paper is an approach to the role of university education with geospatial information technologies, following a position in line with the Integrated Geographic Information Framework, IGIF, which seeks to generate societies link to the management and use of geographic information. The infrastructures or contours of geospatial information provide the appropriation of knowledge that leads to spatial analysis, the training and education strategy defined by the IGIF and establishes criteria for the preparation and awareness of society. The Geographic Information Systems Department of UNED uses a series of resources in its pedagogical mediation to prepare the integration of different alternatives, under a process that is related to positions in accordance with the integrated framework. The object of study consists of analyzing some ways for learning, based on experiences that have been interacting within the university institution. The availability and guarantee of geographic information through a Spatial Data Infrastructure (SDI) represents a way to contribute to the evolution of the information and knowledge society; it is implicitly mentioned that education will play a fundamental role in achieving to different public and private spheres, and to society in general. Education plays the role of facilitating the use and ensuring that it coincides with better territories, based on the interdisciplinary understanding that can favor all
Keywords: Pedagogical mediation, geospatial information, technologies, SDI